2020
DOI: 10.1099/ijsem.0.004286
|View full text |Cite
|
Sign up to set email alerts
|

Clonostachys viticola sp. nov., a novel species isolated from Vitis vinifera

Abstract: A collection of fungal isolates obtained from crop plants, specifically grapevine and blueberry, in Peru were characterised through morphological and DNA sequence analyses of the nuclear ribosomal internal transcribed spacer (ITS), beta-tubulin (tub2) and translation elongation factor 1-alpha (tef-1α) regions. Isolates produced monomorphic and dimorphic conidiophores typical of members of the genus Clonostachys. Single-and multi-locus gene phylogenies confirmed the isolates as representing members of the genus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It revealed that the collection of Clonostachys isolates from coffee and Hemileia uredinia belonged to Clonostachys byssicola , C. rhizophaga and C. rosea . These are well-known taxa that have already been described and discussed in detail in the literature [ 29 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It revealed that the collection of Clonostachys isolates from coffee and Hemileia uredinia belonged to Clonostachys byssicola , C. rhizophaga and C. rosea . These are well-known taxa that have already been described and discussed in detail in the literature [ 29 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clonostachys species have been isolated mainly from soil and litter, but there are also records from bryophytes, wood, bark, black pepper, grapevines, insects, nematodes and even wine [ 46 , 49 , 50 ]. Some Clonostachys species have also been reported as mycoparasites, including Botrytis cinerea , an important pathogen that causes gray mold on numerous crops [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clonostachys Corda, typified by C. araucaria Corda, is characterized by solitary to gregarious, subglobose or globose to ovoid perithecia that are white, yellow, pale orange, tan, or brown; perithecial walls are KOH− and LA−; there are narrowly clavate to clavate asci containing eight ascospores; it produces penicillium-, verticillium-, gliocladium-, or acremonium-like conidiophores, cylindrical to narrowly flask-shaped phialides, and ellipsoidal to subfusiform conidia [ 1 ]. Members of the genus usually have a broad range of lifestyles and occur on the bark of recently dead trees, decaying leaves, and less frequently on other fungi, nematodes, and insects [ 1 , 2 , 3 ]. They are economically important in the fields of pharmaceutics and agriculture [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 100 names have been created under the genus Clonostachys ( (accessed on 1 July 2022)), among which 65 species are commonly accepted [ 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Twenty-four species are known from China [ 2 , 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These known species are commonly found in soils, litter, and dead plant substrata as saprotrophs. They have also been reported as endophytes and epiphytes of living plants (Torcato et al, 2020). Another aspect of the biology of Clonostachys species is their unspecific parasitic ability.…”
Section: Discussionmentioning
confidence: 99%